New type of hot spot cluster centered positioning algorithm and its application - Shao-wu ZHOU; Bo-wei HUANG; Zhao-fu ZENG; Ming-hui ZHOU; Jie ZHAN (Tongxin xuebao)
Considering the facts that the personnel orientation in the coal mine was difficult,and the existing algorithm is of high fixed position error,a new algorithm of hot spot cluster centered positioning for terrain underground in the coal mine was designed.The locations of moving nodes in po ion area were classified by using the RSSI,and the blind spots problems of positioning,which was not explained by the locating method mentioned in the existing literatures,was solved efficiently by means of new algorithm.Besides,the algorithm improved the real time performance and the accuracy of positioning.The validity of new algorithm was verified by the result of numerical simulation and experiment.